Conversion of 1-Octadenaol into Short Chain Alkenes and Alkanes Using Zsia Catalyst and Fluidized Bed Reactor at a Temperature of 400OC - Donatus Setyawan Purwo Handoko; Triyono (PT FORMOSA CENDEKIA GLOBAL, 2023)
Research has been carried out on the catalytic conversion of 1-octadecanol compounds into 1-octadecene alkanes at high temperatures (400oC) in a fluidized bed reactor. The research results obtained are as follows; Hydrogenation of 1-octadecanol was carried out in a fluidized bed reactor. The hydrogenation of 1-octadecanol was carried out in a fluidized bed reactor at a temperature of 400oC with 10 g of ZSiA catalyst and 10 g of pure 1-octadecanol reactant.The results of the study showed the following results: catalytic hydrogenation of 1-octadecanol with ZSiA catalyst at 400oC produced alkanes and alkenes in the chain length range up to C18 reaching 49.60% and the dominant compound produced was 1-octadecene with a relative concentration of up to 20 ,21 %.